On crimes and punishments, and other writings - Beccaria, Cesare, marchese di, 1738-1794.; Bellamy, Richard (Richard Paul); Davies, Richard (Richard Brian), 1944-; Cox, Virginia (Cambridge ; New York : Cambridge University Press, 1995)
This edition of Beccaria's On Crimes and Punishments and other writings presents a radically new interpretation of his thought. Drawing on recent Italian scholarship, Richard Bellamy shows how Beccaria wove together the various political languages of the Enlightenment into a novel synthesis, and argues that his political philosophy, often regarded as no more than a precursor of Bentham's, combines republican, contractarian, romantic and liberal as well as utilitarian themes. The result is a complex theory of punishment that derives from a sophisticated analysis of the role of the state and the nature of human motivation in commercial society. The translation used in this edition is based on the fifth Italian edition, and provides english-speaking readers with Beccaria's own order of his text for the first time. A number of pieces from his writings on political economy and the history of civilisation which were not previously available in English are also included. -- Back cover.
On crimes and punishments --- To Jean Baptiste D'Alembert --- To Andre Morellet --- Inaugural lecture --- Reflections on the barbarousness and the civilisation of nations and on the savage state of man --- Reflections on manners and customs --- Of luxury.
Includes bibliographical references and index.
Keywords: Punishment -- Early works to 1800.; Political science -- Early works to 1800.; Political philosophie; Punishment